A New Perspective: The Implication of Chaos/Complexity Theory in Language through Dichotomies - Zahra Jafari; Ashraf Maibodi; Muhammad Natsir (Randwick International of Education and Linguistics Science Journal, 2020)
This study opens different points of view at chaos/complexity theory (C/CT) which is still a new theory in second language acquisition. Pro. Larsen-Freeman and her colleagues considered a variety of characteristics, C/CT is known as nonlinear dynamics or dynamical system theory that provides a framework for thinking about change over time. Scientists claim that one can see not only the laws of chaos but also those of order, through which a strong explanation for how any collection of components will organize itself and it can be generated in dichotomies. They attempt to rationalize the behavior of large and complex systems, believing they cannot be explained by usual rules of nature